Pemetaaan Partisipatif Potensi Wisata Bantaran Sungai Sebagai Upaya Perencanaan Pembangunan Desa - Lestariningsih, Siti Puji; Ramadhani, Endi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The current management paradigm of the river area is no longer seen as a protected area without any exploitation activity in it. The involvement of the community around the river in the management is an effective alternative inining the sustainable functioning of the riverside area. One of the early approaches to achieving sustainable management of river transportation is by conducting participatory mapping for administrative boundaries and development of tourism activities. The objectives of this activity: 1) provide education on the functioning of the river transport area, potential threats and strategies for sustainable river management; 2) accompany the preparation of participatory maps of the administrative ducks and the development plan of tourist activities in the village of Peniti Besar. Dedication to the community is carried out by the method of community development. The stages are surveys, potential identification, base map making, participatory mapping, map finalisation, and evaluation. Through participatory mapping, the sustainable management of river basin areas based on tourist activities, has provided extensive space for the apparatus of the village, as well as the community in developing its territory independently and intelligently, as listed in the indicator of achievement of the Sustainable Development Goals (SDGs).